2012
DOI: 10.4102/sajip.v38i2.976
|View full text |Cite
|
Sign up to set email alerts
|

Psychological experiences in South African society before the 2010 FIFA World Cup from the systems psychodynamic and positive psychology perspectives

Abstract: <strong>Orientation:</strong> The researchers conducted a literature review to analyse the assumptions of systems psychodynamics, the Tavistock model of group relations, object relations theory and the most relevant constructs in the systems psychodynamic perspective. They then described the assumptions and most relevant constructs in the positive psychology perspective in order to analyse theoretically the psychological effect of large-scale sports events on a community or country. The objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…They found that participation in charity sport events activated each PERMA domain to varying degrees. Meanwhile, Koortzen and Oosthuizen (2012) provided some evidence of PERMA activation in the spectator context, finding that South African residents believed that the 2010 FIFA World Cup would activate positive emotions amongst community members, provide socialisation opportunities, and create a sense of national solidarity. More recently, Pawlowski, Downward, and Rasciute (2014) demonstrated a link between attending sport events and happiness (e.g., pleasure) using data from individuals in 46 countries.…”
Section: Exploring Perma In Spectator Sportmentioning
confidence: 99%
“…They found that participation in charity sport events activated each PERMA domain to varying degrees. Meanwhile, Koortzen and Oosthuizen (2012) provided some evidence of PERMA activation in the spectator context, finding that South African residents believed that the 2010 FIFA World Cup would activate positive emotions amongst community members, provide socialisation opportunities, and create a sense of national solidarity. More recently, Pawlowski, Downward, and Rasciute (2014) demonstrated a link between attending sport events and happiness (e.g., pleasure) using data from individuals in 46 countries.…”
Section: Exploring Perma In Spectator Sportmentioning
confidence: 99%
“…Due to the influence that fans have in the commercial and social advancement of professional clubs, Yoshida, Gordon, Nakazawa and Biscaia (2014) put forward the concept of fan engagement, an interest kindled by the buoyant growth rate of the business of sport globally, which has been resilient despite challenging economic realities (Baller, 2015;Giampiccoli et al, 2015;Koortzen & Oosthuizen, 2012). This resilience has been attributed directly to engagement levels of fans globally, who have continued and even enhanced their expenditure on the activities of their favourite professional clubs -despite the pressures of a declining global economic climate (Bing et al, 2015;Giampiccoli et al, 2015;Madrigal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…South African football in recent years has experienced development and enjoyed marketable and profitable growth due to the popularity of the Premier Soccer league (PSL) as purported by Stander and Van Zyl (2016) and Koortzen and Oosthuizen (2012). Moreover, the fan base of PSL teams has grown exponentially over the years, making it one of the most popular football leagues across the African continent.…”
Section: Introductionmentioning
confidence: 99%